Sexual functioning in 4, 418 postmenopausal women participating in UKCTOCS: a qualitative free-text analysis. Issue 10 (October 2019) - Harder, Helena; Starkings, Rachel M.L.; Fallowfield, Lesley J.; Menon, Usha; Jacobs, Ian J.; Jenkins, Valerie A.
Abstract: Objective: Sexual well-being can contribute significantly to the overall quality of women's lives. This qualitative study aimed to examine sexual activity, functioning, and satisfaction in a large sample of postmenopausal women from the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) Methods: Thematic analysis was used to evaluate the free-text data of the Fallowfield Sexual Activity Questionnaire (FSAQ) completed by UKCTOCS participants at baseline before annual screening. Results: A total of 24, 305 women completed the baseline FSAQ and 4, 525 (19%) provided free-text data, with 4, 418 comments eligible for analysis. Median age was 64 years; 65% had a partner and 22.5% were sexually active. Four interrelated themes were derived: partner availability, physical and sexual health, mental well-being, and interpersonal relationships. Primary reason for absence of sexual activity was lack of a partner, mainly due to widowhood ( n = 1, 000). Women discussed how partner's medical condition (27%) or sexual dysfunction (13.5%), their own physical health (18%) or menopause-related symptoms (12.5%), and prescribed medication (7%) affected sexual activity. Impact of low libido in self (16%) or partner (7%), relationship problems (10.5%) or logistics (6%), and perceptions of ageing (9%) were also mentioned. Few (3%) referred to positive sexual experiences or had sought medical help for sexual problems (6%). Conclusions: This qualitative analysis explored postmenopausal women's perspective on their sexual functioning. Having an intimate partner and good physical health are key factors for continuation of sexual activity and satisfaction. Further sexual education for healthcare professionals is needed to raise awareness about sexuality and sexual difficulties in later life. N/A: Video Summary: Supplemental Digital Content 1, http://links.lww.com/MENO/A426 . Abstract : Supplemental Digital Content is available in the text